2020
DOI: 10.1038/s41467-020-19151-8
|View full text |Cite
|
Sign up to set email alerts
|

Rapid and robust assembly and decoding of molecular tags with DNA-based nanopore signatures

Abstract: Molecular tagging is an approach to labeling physical objects using DNA or other molecules that can be used when methods such as RFID tags and QR codes are unsuitable. No molecular tagging method exists that is inexpensive, fast and reliable to decode, and usable in minimal resource environments to create or read tags. To address this, we present Porcupine, an end-user molecular tagging system featuring DNA-based tags readable within seconds using a portable nanopore device. Porcupine’s digital bits are repres… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
33
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 40 publications
(33 citation statements)
references
References 17 publications
0
33
0
Order By: Relevance
“…[ 31 ] We have demonstrated that nanopore sensing might be an alternative readout method for DNA tags in comparison to nanopore sequencing. [ 32 ] We created multiple copies of a specific data file written in a DNA structural annotation that can expand the potential of DNA nanostructures and nanopores as a feasible way to archive and access data.…”
Section: Discussionmentioning
confidence: 99%
“…[ 31 ] We have demonstrated that nanopore sensing might be an alternative readout method for DNA tags in comparison to nanopore sequencing. [ 32 ] We created multiple copies of a specific data file written in a DNA structural annotation that can expand the potential of DNA nanostructures and nanopores as a feasible way to archive and access data.…”
Section: Discussionmentioning
confidence: 99%
“…It is important to note the distinction between uses of the term DNA barcoding, as DNA barcoding is used for classifying species (different gene regions function as barcodes to identify organisms) 39,40 , to study molecular systems (for example in the form of unique molecular identifiers to eliminate PCR bias) 41 , or to tag products [42][43][44] . A molecular product tag is a pre-defined amount of DNA that is added to the building blocks of a certain substance.…”
Section: Logic Gates and Circuitsmentioning
confidence: 99%
“…[ 8–10 ] Data decoding of DNA nanostructure‐based storage is often based on gel electrophoresis, which severely restricted the reading speed and data capacity. As an emerging technique, nanopore sequencing has been utilized to decode data saved in DNA sequences with advantages in terms of cost and readout speed, [ 11–14 ] but it is almost helpless for DNA nanostructure‐based storage. Even if the sequence is decoded, it is still difficult to reproduce the whole structure accurately, which indicates the higher security of this storage method from this perspective.…”
Section: Introductionmentioning
confidence: 99%
“…
and readout speed, [11][12][13][14] but it is almost helpless for DNA nanostructure-based storage. Even if the sequence is decoded, it is still difficult to reproduce the whole structure accurately, which indicates the higher security of this storage method from this perspective.
…”
mentioning
confidence: 99%